Heterologous expression reveals the biosynthesis of the antibiotic pleuromutilin and generates bioactive semi-synthetic derivatives. Issue 1 (December 2017) - Alberti, Fabrizio; Khairudin, Khairunisa; Venegas, Edith; Davies, Jonathan; Hayes, Patrick; Willis, Christine; Bailey, Andy; Foster, Gary
Abstract The rise in antibiotic resistance is a major threat for human health. Basidiomycete fungi represent an untapped source of underexploited antimicrobials, with pleuromutilin—a diterpene produced byClitopilus passeckerianus —being the only antibiotic from these fungi leading to commercial derivatives. Here we report genetic characterisation of the steps involved in pleuromutilin biosynthesis, through rational heterologous expression inAspergillus oryzae coupled with isolation and detailed structural elucidation of the pathway intermediates by spectroscopic methods and comparison with synthetic standards.A. oryzae was further established as a platform for bio-conversion of chemically modified analogues of pleuromutilin intermediates, and was employed to generate a semi-synthetic pleuromutilin derivative with enhanced antibiotic activity. These studies pave the way for future characterisation of biosynthetic pathways of other basidiomycete natural products in ascomycete heterologous hosts, and open up new possibilities of further chemical modification for the growing class of potent pleuromutilin antibiotics. Pleuromutilin derivatives are potent antibacterial drugs obtained from Basidiomycete fungi. Here, the authors report the genetic characterisation of the steps involved in pleuromutilin biosynthesis through heterologous expression and generate a semi-synthetic pleuromutilin derivative with enhanced antibiotic activity.